Forjando lideranças : comportamentos políticos e atuação no Sindicato dos Metalúrgicos de Belo Horizonte e Contagem durante a ditadura militar (1964-1985) - Carolina Dellamore Batista Scarpelli (2019)
This study aims at restructuring the political behaviour of workers’ leadership and political and union activists who took part in the Belo Horizonte and Contagem metalworkers’union during the military dictatorship (1964-1985). The purpose is to understand the impacts of the period and their effects on the union, which commenced with the military coup of 1964, with the removal of the elected union’s board of directors, the designation of intervenors by the Ministry of Labor and the revocation of its main leading members, as well as the establishment of a quiet resistance, the role of union activists and left-wing political militants n the strike movement of 1968, in the industrial hub of Contagem, prompting another government intervention in the labor organization. It also examines the strugles between the elected board of directors in 1969 – who had been in charge of the union for fifteen years – and the new political forces in the region, which resulted in the union opositions that emerged in the decades of 70’s and 80’s. It is also viewed here the action plans of these groups, the return of the strikes as part of political struggle as well as the introduction of male and female steelworkers in the ‘Movimento Contra a Carestia’ (labor movement against the cost of living), in the campaign for amnesty and for ‘Diretas Já Campaign!’, and also the innovative experience of Centro Cultural Operário (labor cultural center) and the female workers’ battle to gain more participation in the union. The Investigation of workers leading efforts, political militancy and union activism made it possible to identify resistance and political engagement against dictatorship, collaboration with the regime and conciliatory strategies in the face of military dictatorship. Therefore, metalworkers’ union of Belo Horizonte and Contagem served as a starting point to understand more comprehensively the social attitudes of male and female workers during the Brazilian military dictatorship.